The big easy - Imson, Donna Marie; VStudios ([S.l.] : VStudios, 2008)
Donna Imson tackles the reasons behind the prevalent unethical practices in network marketing and its adverse effect in upline and the importance of constantly seeking the path of learning
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing